Evaluating Violent Person Management Training for Medical Students in an Emergency Medicine Clerkship. Issue 9 (September 2015) - Ball, Caroline A.; Kurtz, Alicia M.; Reed, Trent
<x xml:space="preserve">Abstract</x> Objectives Violence is a significant problem facing healthcare workers in the United States, particularly in emergency departments (EDs). Education is key to providing a safe environment for workers to ensure their ability to recognize and respond to violent patients and visitors. We studied the effects of a video podcast–based violence education program aimed at improving medical students' knowledge and confidence in identifying and responding to violence. Methods We provided a pretest and questionnaire about recognizing and responding to violence in the ED to 141 fourth-year medical students on the first day of their emergency medicine clerkship. Students were invited to view a video podcast addressing violent person management (VPM) in the ED and were then administered a posttest and questionnaire at the conclusion of the clerkship. We measured changes in knowledge and confidence in responding to violent situations of students who watched the video podcast and completed the pre- and posttests and questionnaires. In addition, we assessed student response to the video podcast format as well as quantified student exposure to violence during their clerkship. Results Of the 123 students who completed the pre- and posttests, 93 (75.6%) reported watching the video. These 93 students demonstrated a statistically significant improvement in exam score between the pre- and posttests and expressed increased confidence in responding to violence in the ED. A total of 66 (71.0%) agreed that the video lecture was an appropriate method to deliver the VPM material and 4 (4.3%) disagreed. Seventy-two (77.4%) students agreed the VPM content was professionally relevant to medical students during the emergency medicine clerkship and only 1 student (1.1%) disagreed. Almost half of the 141 students surveyed witnessed verbal or physical assault in the ED during their 4-week clerkship. Conclusions An educational video podcast is an effective method to improve medical students' knowledge and confidence in responding to a potentially violent person or violent situation in the ED and may be useful in other healthcare settings.